Pendampingan Renovasi Façade Bangunan pada Masjid Al-Mizan, Rawamangun, Jakarta Timur - Desy Mariani (Indonesian Journal of Emerging Trends in Community Empowerment, 2026)
The previous Community Assistance Activity at the Al-Mizan Mosque was the minaret renovation. For the next stage, the Al-Mizan Mosque DKM represents the congregation who intends to align the building facade with the new minaret. DKM wants the facade design to keep maintain a modern design concept, by applying geometric shapes and choosing modern materials. Here's the ACP used in dark blue, light blue and gray will be presented on the facade of the mosque so that it is more in harmony with the new minaret. So the Al-Mizan Mosque DKM partnered with the Budi Luhur University Community Services Team to plan a facade renovation that was in line with the minaret design. The output is in the form of design drawings with visualizations that are needed as an initial overview of the renovation and subsequently to raise donations. Apart from that, DKM also wants renovation supervision to be more effective and efficient, especially regards to quality, cost and time. Community Services is carried out through the early discussions with DKM in formulating the facade concept and cost description. After that, the Budi Luhur University Team provided output in the form of a plan drawing and Bill of Quantity to the DKM. In carrying out the renovation process, we are still assisted, especially about the technical considerations during the renovation.